Harmful practices in the management of childhood diarrhea in low- and middle-income countries: a systematic review - Carter, Emily (BMC Public Health, 2015)
BACKGROUND: Harmful practices in the management of childhood diarrhea are associated with negative health outcomes, and conflict with WHO treatment guidelines. These practices include restriction of fluids, breast milk and/or food intake during diarrhea episodes, and incorrect use of modern medicines. We conducted a systematic review of English-language literature published since 1990 to assess the documented prevalence of these four harmful practices, and beliefs, motivations, and contextual factors associated with harmful practices in low- and middle-income countries. METHODS: We electronically searched PubMed, Embase, Ovid Global Health, and the WHO Global Health Library. Publications reporting the prevalence or substantive findings on beliefs, motivations, or context related to at least one of the four harmful practices were included, regardless of study design or representativeness of the sample population. RESULTS: Of the 114 articles included in the review, 79 reported the prevalence of at least one harmful practice and 35 studies reported on beliefs, motivations, or context for harmful practices. Most studies relied on sub-national population samples and many were limited to small sample sizes. Study design, study population, and definition of harmful practices varied across studies. Reported prevalence of harmful practices varied greatly across study populations, and we were unable to identify clearly defined patterns across regions, countries, or time periods. Caregivers reported that diarrhea management practices were based on the advice of others (health workers, relatives, community members), as well as their own observations or understanding of the efficacy of certain treatments for diarrhea. Others reported following traditionally held beliefs on the causes and cures for specific diarrheal diseases. CONCLUSIONS: Available evidence suggests that harmful practices in diarrhea treatment are common in some countries with a high burden of diarrhea-related mortality. These practices can reduce correct management of diarrheal disease in children and result in treatment failure, sustained nutritional deficits, and increased diarrhea mortality. The lack of consistency in sampling, measurement, and reporting identified in this literature review highlights the need to document harmful practices using standard methods of measurement and reporting for the continued reduction of diarrhea mortality. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-2127-1) contains supplementary material, which is available to authorized users.